ANALYSIS OF IMPLEMENTING AUTHENTIC ASSESSMENT OF CURRICULUM 2013 BY HIGH SCHOOL BIOLOGY TEACHERS - Novia Elyza Melinda; Indayana Febriani Tanjung (Jurnal Pelita Pendidikan, 2022)
The purpose of this study is to describe how the application of authentic assessment conducted by high school/vocational biology teachers in Langkat Regency. This study used a qualitative approach with the type of direct survey research. The sample used in this study was 15 samples of Biology Teachers From 4 different high schools in Langkat Regency including SMA Negeri 1 Stabat, SMA Negeri 1 Tanjung Pura, SMAS Preparation Stabat and SMAS Tunas Bangsa. Authentic assessment includes several aspects, namely behavior, knowledge and skills or talents. But in reality, from the results of questionnaires, interviews, and observations, it was found that the results of implementing authentic assessment had not been fully carried out by some biology teachers. Obstacles experienced by biology teachers in authentic assessment include the lack of training for biology teachers, delivery of material during training makes biology teachers less able to understand authentic assessment and explain all aspects contained in the 2013 curriculum, the number of students who must be assessed individually by biology teachers, limited time to conduct assessments, and the facilities and infrastructure available at schools have not been used optimally. The large number of students who are assessed individually requires a lot of time to carry out the assessment. Therefore, teachers feel confused in dividing their time in advance with infrastructure that cannot be utilized optimally.